Enterprise Interoperability IV 2010
DOI: 10.1007/978-1-84996-257-5_12
|View full text |Cite
|
Sign up to set email alerts
|

Model for Trans-sector Digital Interoperability

Abstract: Interoperability refers to the ability of two or more systems or components to exchange information and to use the information that has been exchanged. The importance of interoperability has grown together with the adoption of Digital Information Networks (DINs). DINs refer to information networks supported by telecommunication infrastructures and terminated by microprocessors. With an upcoming interest in services science and trans-sector business models, a stronger driver arises to further break the interope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…We demonstrated that our framework has a much wider application range than the DUT and MIT frameworks. For example: 1) to make the development of information networksupported services more systematic [112]; 2) to investigate levels of economic cross-sectoral IT infrastructure interoperability [111]; and 3) to be used by Eurostat to redesign their surveys in a more conceptually valid way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated that our framework has a much wider application range than the DUT and MIT frameworks. For example: 1) to make the development of information networksupported services more systematic [112]; 2) to investigate levels of economic cross-sectoral IT infrastructure interoperability [111]; and 3) to be used by Eurostat to redesign their surveys in a more conceptually valid way.…”
Section: Discussionmentioning
confidence: 99%
“…An important implication results from focusing in the intermediate processes without specifying the end-to-end observables: a variety of other applications becomes obvious. In parallel with value assessment, we are investigating two other applications for our framework: service design [112] and infrastructure interoperability [111]. But even within value assessment, the evolutionary holonic approach brings a significant difference to the concept of value than the one understood by the MIT and the DUT frameworks.…”
Section: Figmentioning
confidence: 99%